Development of a nurse-manager dualistic intervention program to alleviate burnout among nurses based on the appreciative inquiry - Guo, Yu-Fang; Wang, Xin-Xin; Yue, Fang-Yan; Sun, Feng-Ye; Ding, Min; Jia, Yan-Nan (Frontiers in Psychology, 2022)
Aims: To develop an feasible and effective nurse-manager dualistic intervention program to support nurses coping with burnout symptoms. Background: Person-organization combined interventions were recommended as the most effective approach for reducing burnout symptoms. However, few were developed in the nursing field. Methods: The Medical Research Council, United Kingdom (MRC UK) Framework for Development and Evaluation of Complex Interventions was employed for nurse-manager dualistic intervention program development. Three steps were followed for developing the dualistic intervention program: (1) identifying the evidence base by conducting extensive reviews of the relevant literature and a mixed study; (2) identifying/developing theory by selecting the Job Demands-Resources model and proposing the theoretical framework for intervention development; (3) modifying the process and outcomes of the nurse-manager dualistic intervention program. Results: The intervention program consists of six group sessions over 9 weeks. Researchers/managers are supposed to deliver the program. The main contents of the intervention are: (1) inception (session 1); (2) discovery (session 2); (3) dream (session 3); (4) design (session 4); (5) destiny (session 5); (6) keep (session 6). The emphasis of the intervention is on helping nurses dealing with burnout symptoms. Conclusion: Followed the guidance of MRC framework, an feasible and potentially effective nurse-manager dualistic intervention program was developed for nurses coping with burnout. Future studies are needed to model the intervention and assess the effects and replicability of the intervention.